Penerapan Teknik Inside Outside Circle Dalam Mengenalkan Huruf Abjad - Alfan Hadi; Silvia Yolanda; Nursiah (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2025)
The objectives of this study were, among others: 1) To find out how the learning process uses the inside outside circle technique in introducing alphabets to group A children at RA Al-Mahmud Aik Ampat. 2) To determine the learning outcomes of group A children at RA Al-Mahmud Aik Ampat by using the inside outside circle technique. This type of research is Classroom Action Research (PTK). Data sources refer to primary sources from the research title, while secondary sources from journals or previous research. Data collection techniques using observation, tests and documentation data analysis techniques using qualitative and quantitative. The results showed, among others: The results of the learning outcomes test after the implementation of learning with the inside-outside circle learning model continued to increase and showed that the inside-outside circle learning model proved effective for improving the learning outcomes of class A students at RA Al-Mahmud Aik Ampat. The implications of this research for Islamic educational institutions are to always develop human resources with various forms of creativity and innovation. This research is a source of reference or previous research for other studies.